The Block Principal Pivoting Algorithm for the Linear Complementarity Problem with an M-Matrix. (30th July 2019) - Fang, Xi-Ming; Qiao, Zhi-Jun; Zhao, Heng-Jun
Abstract : The principal pivoting algorithm is a popular direct algorithm in solving the linear complementarity problem, and its block forms had also been studied by many authors. In this paper, relying on the characteristic of block principal pivotal transformations, a block principal pivoting algorithm is proposed for solving the linear complementarity problem with anM -matrix. By this algorithm, the linear complementarity problem can be solved in some block principal pivotal transformations. Besides, both the lower-order and the higher-order experiments are presented to show the effectiveness of this algorithm.